"Habla, flaquita. ¿Bajas?" Prácticas de cortejo de jóvenes hombres heterosexuales en Tinder - Ayala Castro, Gloria Estrellita (2023)
This article investigates the behavior of heterosexual users on Tinder, focusing on profile setup and masculinity expectations. Firstly, it examines how masculinity norms influence the creation of their profiles. Participants follow presentation patterns, demonstrating the flexibility of masculinities on the platform. Secondly, it explores perceptions of masculinity in profile construction, showing that users value authenticity and seek to avoid appearing desperate, expressing interest in more meaningful relationships. Thirdly, it analyzes the implementation of courtship in the virtual environment. Profile evaluation primarily centers on photos, followed by openness, originality, and a sense of humor in interactions. The importance of maintaining a balance in interest and avoiding inappropriate behaviors is highlighted. Social media exchange dynamics and mutual trust are crucial for arranging an in-person meeting. In summary, the influence of hegemonic masculinities and the emergence of alternative models are observed in courtship practices on dating apps.